Socialization of Smart Investment, Not Fake Investment in Cipagalo Village, Bojongsoang Subdistrict, Bandung Regency - Yudi Zatnika; Iin Safariah; Nia Kurniasih; Erna Nurhasanah; Derri Benarli Nugraha; Dasep Heriansyah (Pascasarjana Universitas Mataram, 2025)
This study aims to describe the implementation and outcomes of the community service program “Smart Investment, Not Fake” designed to improve investment literacy in Cipagalo Village, Bojongsoang Subdistrict, Bandung Regency, Indonesia. Many residents are exposed to attractive but unclear investment offers and have limited ability to distinguish legal products from fraudulent schemes, underscoring the need for education on safe investing. The research used a descriptive, pre-experimental one-group pre-test–post-test design. The program was conducted face-to-face on 1 February 2025 and involved 30 villagers selected through purposive sampling. The intervention consisted of a structured socialization session including lectures, interactive discussions, and the administration of pre-test and post-test questionnaires on knowledge of smart and fake investments. Data were analyzed descriptively by comparing scores and response patterns before and after the session. The pre-test results showed that 90.90% of participants did not yet understand smart and fake investments. After the session, 93.33% rated the material as very good, 100% reported understanding the concepts and the importance of safe, OJK-supervised investment, and 36.36% stated that they intended to apply the new knowledge in practice. Participants' high attendance, active engagement, and requests for similar activities with other topics indicated strong community interest and perceived relevance. The study concludes that a short, structured socialization program, implemented through collaboration between university lecturers and local stakeholders, can effectively increase village-level financial literacy and help reduce vulnerability to investment fraud. Future activities should refine instruments to suit varying literacy levels.